(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The purpose of this article is to discuss some interpretative controversies that may arise from the provisions contained in Law No. 13,869/2019, in force since January 3, 2020. In this regard, initially, it will be presented the context in which the new law was promulgated, which abrogated the old legal diploma that regulated the matter (Law No. 4,898/1965). In continuity, it will be discussed the need for the control exercised by Criminal Law of the conduct of state agents in order to repress the abuse of authority. At the end, a critical analysis of the new legislation, especially in relation to the requirement of the special subjective element of the unjust, and also of some controversial aspects of the normative precepts and their inevitable judicialization will be presented.